2016
DOI: 10.3102/0034654316628993
|View full text |Cite
|
Sign up to set email alerts
|

Critical Discourse Analysis in Education

Abstract: This article reviews critical discourse analysis scholarship in education research from 2004 to 2012. Our methodology was carried out in three stages. First, we searched educational databases. Second, we completed an analytic review template for each article and encoded these data into a digital spreadsheet to assess macro-trends in the field. Third, we developed schemata to interpret the complexity of research design. Our examination of 257 articles reveals trends in research questions, the theories researche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 125 publications
(141 reference statements)
0
26
0
2
Order By: Relevance
“…Finally, we employ discourse analysis in order to develop a deeper understanding of the themes and messages conveyed in the policy frameworks and statements. Several previous studies have demonstrated that discourse analysis and critical discourse analysis can be effective tools for the analysis of educational practices and policies (Lester, Lochmiller, & Gabriel, 2016Liasidou, 2008;Rogers et al, 2016;Taylor, 2004). Discourse analysis, according to van Dijk (1993), seeks to understand "the role of discourse in the (re)production and challenge of dominance [italics in original]" in order to draw out the deeper meanings and relationships represented in the policy statements (p. 283).…”
Section: Methodsmentioning
confidence: 99%
“…Finally, we employ discourse analysis in order to develop a deeper understanding of the themes and messages conveyed in the policy frameworks and statements. Several previous studies have demonstrated that discourse analysis and critical discourse analysis can be effective tools for the analysis of educational practices and policies (Lester, Lochmiller, & Gabriel, 2016Liasidou, 2008;Rogers et al, 2016;Taylor, 2004). Discourse analysis, according to van Dijk (1993), seeks to understand "the role of discourse in the (re)production and challenge of dominance [italics in original]" in order to draw out the deeper meanings and relationships represented in the policy statements (p. 283).…”
Section: Methodsmentioning
confidence: 99%
“…The critical discourse analysis has enabled us to deconstruct these differences to understand that decisions made about meaning in RE have implications for how RE departments address issues of power, identity, agency and difference. From a traditional CDA perspective, this alerts us to the potential for misuse of power, misrepresentation of identity and difference or constraint on autonomy and so it would seem reasonable to conclude with some elaboration of these themes, however, Rogers et al (2016) explain how, over time, CDA results have become much more inclusive of reconstructive frameworks. As a result, in the findings from contemporary CDA studies, in addition to a critical analysis of power structures, there is likely to be a discussion of the potential for agents within those structures to affect change through identifying social relations which have the potential for leading to 'emancipatory ends' (Rogers et al 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, critical discourse and inquiry, becoming increasingly popular ways to frame teaching and learning in higher education (Rogers et al, 2016) with a focus on collaborative discussion and problem-solving across leadership preparation instruction (Jenkins, 2020), were also emphasized strategies for the CPED instructors as noted across seven syllabi course overviews. Students from this CPED program are also expected to become skilled in a type of critical discourse -the two-way change process of leadership (Fairholm, 2014) -within the principal investigator's change leadership course.…”
Section: Process Evaluationmentioning
confidence: 99%